Revealing the endophytic mycoflora in tea (Camellia sinensis) leaves in Sri Lanka: the first comprehensive study - Thambugala, Kasun; Daranagama, Dinushani; Kannangara, Sagarika; Kodituwakku, Thenuka (Phytotaxa, 2021)
Endophytic fungi are a diverse group of microorganisms that live asymptomatically in healthy tissues of host and they have been reported from all kinds of plant tissues such as leaves, stems, roots, flowers, and fruits. In this study, fungal endophytes associated with tea leaves (Camellia sinensis) were collected from Kandy, Kegalle, and Nuwara Eliya districts in Sri Lanka and were isolated, characterized, and identified. A total of twenty endophytic fungal isolates belonging to five genera were recovered and ITS-rDNA sequence data were used to identify them. All isolated endophytic fungal strains belong to the phylum Ascomycota and the majority of these isolates were identified as Colletotrichum species. Phyllosticta capitalensis was the most commonly found fungal endophyte in tea leaves and was recorded in all three districts where the samples were collected. This is the very first investigation on fungal endophytes associated with C. sinensis in Sri Lanka based on molecular sequence data. In addition, a comprehensive account of known endophytic fungi reported worldwide on Camellia sinensis is provided.